Policy, Place, and Promotion: Predictors of Early Smoking in a Rural Health Setting - Hidayat, Useng; Indasah, Indasah; Puspitasari, Yenny; Mochamad Salman Hasbyalloh (Babali Publisher, 2025)
Introduction: Adolescent smoking continues to pose a major public health challenge, with the WHO reporting that nearly 22% of adolescents globally have tried smoking, and national data in Indonesia showing prevalence rates among junior high school students exceeding 10%. Early initiation not only increases the risk of long-term nicotine dependence but also disrupts physical and psychosocial development. This study analyzed the influence of smoke-free policy implementation, availability of smoking places, and exposure to cigarette advertisements on early smoking behavior among junior high school adolescents in the Tanjungsiang Health Center working area. Methods: A cross-sectional design was used with 101 randomly selected respondents, and data were collected using a validated questionnaire. Results: The findings revealed that most respondents were 14 years old and in grade VIII, with moderate smoking behavior as the dominant category. Stricter smoke-free area (KTR) implementation significantly reduced smoking behavior, while designated smoking places showed only a weak association. In contrast, cigarette advertisement exposure showed no significant association. Conclusion: These results underscore the critical role of policy enforcement in curbing adolescent smoking. Strengthening KTR enforcement, particularly in schools and community environments, represents a practical strategy to prevent early initiation and promote healthier adolescent development in rural settings.